Distribution and predictors of haemophilia-related costs in the United Kingdom: analysis of the CHESS I and CHESS II burden of illness studies - Ione Woollacott; Amit Chhabra; Tom Burke; Jack Brownrigg; Lucy Richardson; Enrico Ferri Grazzi; Jamie O’Hara; Josie Godfrey; Michael Laffan (BMC Health Services Research)
Abstract Background Few studies have evaluated direct medical or societal costs of haemophilia in the United Kingdom (UK), and how patient characteristics impact future costs is uncertain. Cost predictors were identified and examined using cross-sectional data from the CHESS I and II studies. Methods Patient- and physician-reported outcomes were analysed for UK adult males aged ≤ 65, with haemophilia A or B and no recent clinical trial participation. Demographics, haemophilia type and severity, inhibitors, annual bleed rate (ABR), problem joints (PJs), treatment type, and comorbidities, were utilised in regression analyses. Health-related quality of life was assessed using EQ-5D. Generalised linear models estimated expected non-drug haemophilia-related direct medical costs (DMC) and societal costs (non-drug DMC, direct non-medical and indirect costs). Average marginal effects (AMEs) determined predictors of cost. Results Costs for 378 patients were analysed. Mean age was 33 years and 79% (299) had haemophilia A. Mean annual per-patient DMC were £165,001 (including factor treatment costs) and £4,091 when excluding factor replacement treatment costs (non-drug DMC). Mean annual per-patient non-treatment societal costs were £11,550 (standard deviation £20,171) among those with data available (n = 51). Number of PJs, ABR, and treatment regimen were significant determinants of haemophilia-related non-drug DMC (all P < 0.001). Non-drug DMC increased as ABR increased (AMEs were £2,018 for ABR 1–5, £3,101 for ABR 6–10 and £5,785 for ABR ≥ 11, vs. ABR 0) and by £1,869 per additional PJ. No significant predictors of non-drug haemophilia-related societal costs were identified. Mean EQ-5D score was 0.66, with lower scores observed for people with haemophilia B (0.48) compared with haemophilia A (0.71) and with increasing haemophilia severity. Conclusions UK direct medical and societal costs of haemophilia are substantial. Non-drug DMC were particularly associated with ABR and number of PJs. These findings may be useful for real-world evaluations of the economic burden of haemophilia in the UK.